If it's not what You are looking for type in the equation solver your own equation and let us solve it.
66=z-11
We move all terms to the left:
66-(z-11)=0
We get rid of parentheses
-z+11+66=0
We add all the numbers together, and all the variables
-1z+77=0
We move all terms containing z to the left, all other terms to the right
-z=-77
z=-77/-1
z=+77
| 5(3x+9)=-38+23 | | 8^(x+1)=25 | | 3=a+4+6 | | 1+2p+5=-2 | | 5x+11=3x+63 | | 88+c=500 | | 5x-(-12x+20)=-3 | | -5/6=u+6 | | 3x-6=6x=3 | | 6-5n+8n=12 | | 0=-3-8(-5a-1) | | 2x=14.6 | | 11x^2=24 | | 2(a+4)-7=1÷2(5+2a) | | 5(u-8)=7u-44 | | .18x=117 | | .03y+67=1 | | -88=-6(2r-2)-4 | | -7w+3(w-6)=10 | | 3.048=k-2.84 | | 6-2p=20 | | .18*x=117 | | -8+5(7x-2)=157 | | 5(6x+10)=24x-4 | | 0.343*0.343=x | | −13=r/9+8 | | 4(3.5x)-6x=21.6 | | 5m-1/6=3m-4/4 | | 6a-20=2 | | -3x2+50=0 | | 2*6+2*x=2(6+3 | | 20-6a=2 |